Effects of Second Language Learning on the Plastic Aging Brain: Functional Connectivity, Cognitive Decline, and Reorganization - Bubbico, Giovanna; Chiacchiaretta, Piero; Parenti, Matteo; di Marco, Marcin; Panara, Valentina; Sepede, Gianna; Ferretti, Antonio; Perrucci, Mauro Gianni (Frontiers in Neuroscience, 2019)
Learning a new language requires the use of extensive neural networks and can represent a potent tool to reorganize brain neuroplasticity. In this study, we analyze how 4-month long second language learning program (16, 2-h sessions) can lead to functional changes in the brain of healthy elderly individuals. A large number of studies point out a declining of brain-skills with age; here we analyze how cognition together with functional brain organization can be improved late in life. Twenty-six older adults (59 to 79 years old) were enrolled in the present study. A complete neuropsychological examination was administered pre- and post-intervention to measure global cognition level, short- and long-term memory, attention, language access, and executive functions. After the program, in the intervention group, we observed a significant improvement in global cognition together with increased functional connectivity in the right inferior frontal gyrus, right superior frontal gyrus and left superior parietal lobule. These findings can be added to the current neurobiological breakthroughs of reshaping brain networks with a short language learning practice in healthy elderly subjects. We, therefore, suggest that learning a foreign-language may represent a potentially helpful cognitive intervention for promoting healthy aging.